Neutrophil-to-Lymphocyte Ratio: A Predictor of Hospital Stay Duration in Acute Cholecystitis - Khomusi, Munira Murtaza; Perveen, Sughra; Iqbal, Mazhar; Ahmed, Tanweer; Seth, Uzma Shamim; Ali, Jehangir (Medical Science: Trends and Innovations Vol. 5, 2025)
Aim: The aim of the study was to assess the neutrophil-to-lymphocyte ratio (NLR) as a predictor of the length of hospital stay in patients with acute cholecystitis. Methods: From November 2020 to April 2021, a cross-sectional observational study was conducted at Jinnah Postgraduate Medical Center's Ward-3 in Karachi. Patients with acute cholecystitis diagnosed by clinical history, examination, and ultrasonography were included; they ranged in age from 30 to 50. All were given painkillers, antibiotics, and intravenous fluids. After six weeks, an interval cholecystectomy was scheduled, and hospital discharge was decided by the resolution of tenderness, normalisation of temperature, and normalisation of pulse. The length of hospitalisation was compared for patients with NLR \(\le\)3 (normal) and >3 (deranged). SPSS Version 25 was used to record and analyse information on the length of stay, age, gender, clinical findings, and differential leukocyte count. Results: A total of ninety patients were included: ten males (11.11%) and eighty females (88.88%). Patients with deranged ratios were sixty-five (72.22%) and normal ratios were twenty-five (27.77%). The length of hospital stay was recorded as five to eight days for deranged ratio and three to five days for the normal ratio respectively. Ten patients (11.11%) had gangrenous gall bladder and underwent open cholecystectomy. Conclusion: In this study, patients with neutrophil to lymphocyte ratio greater than three had advanced acute cholecystitis and underwent open surgery. Neutrophil to lymphocyte ratio of greater than three corresponds to longer hospital stays and complications.